1984
DOI: 10.1017/s0022112084002743
|View full text |Cite
|
Sign up to set email alerts
|

Active cancellation of pure tones in an excited jet

Abstract: This paper describes the results of experiments conducted on a circular jet simultaneously excited by two different acoustic tones. By varying the phase between two signals at harmonically related frequencies, control can be exercised on the process of harmonic generationsometimes the process being virtually destroyed. This is shown to be so for both harmonic and subharmonic generation, but the latter is more difficult to control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Some of these studies focus on shear layer control and use excitation at the separation point [243][244][245][246][247][248][249][250], mechanical actuation [248,[251][252][253], or transverse excitation of the free stream by both standing waves [254] and traveling waves [237,[255][256][257]. Experiments…”
Section: Transverse Forcing Of Typical Combustor Flow Fieldsmentioning
confidence: 99%
“…Some of these studies focus on shear layer control and use excitation at the separation point [243][244][245][246][247][248][249][250], mechanical actuation [248,[251][252][253], or transverse excitation of the free stream by both standing waves [254] and traveling waves [237,[255][256][257]. Experiments…”
Section: Transverse Forcing Of Typical Combustor Flow Fieldsmentioning
confidence: 99%
“…This seminal work initiated many experimental studies which revealed the large potential of active control techniques. [15][16][17][18][19][20][21][22][23] In this paper, we combine passive and active flow control techniques to rectangular turbulent jets, and analyse the resulting flow field. The former is obtained by using a rectangular shape with various aspect ratios of the jet and the latter is obtained by imposing at the jet inlet an excitation with a specific amplitude and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have used active control methods to influence the generation and pairing of the primary vortex rings. [3][4][5] In most cases, the jet is ''forced'' by superposing oscillating components on the mean nozzle exit velocity. Control of the dimensionless forcing frequency or frequencies ͑Strouhal number͒ allows control of vortex ring spacing and axial pairing locations.…”
Section: Introductionmentioning
confidence: 99%